Tensions on the actin cytoskeleton and apical cell junctions in the C. elegans spermatheca are influenced by spermathecal anatomy, ovulation state and activation of myosin - Sadeghian, Fereshteh; Grooms, Noa W. F.; Chung, Samuel H.; Cram, Erin J. (Frontiers in Cell and Developmental Biology, 2024)
Introduction Cells generate mechanical forces mainly through myosin motor activity on the actin cytoskeleton. In C. elegans, actomyosin stress fibers drive contractility of the smooth muscle-like cells of the spermatheca, a distensible, tube-shaped tissue in the hermaphrodite reproductive system and the site of oocyte fertilization. Stretching of the spermathecal cells by oocyte entry triggers activation of the small GTPase Rho. In this study, we asked how forces are distributed in vivo, and explored how spermathecal tissue responds to alterations in myosin activity. Methods In animals expressing GFP labeled actin or apical membrane complexes, we severed these structures using femtosecond laser ablation and quantified retractions. RNA interference was used to deplete key contractility regulators. Results We show that the basal actomyosin fibers are under tension in the occupied spermatheca. Reducing actomyosin contractility by depletion of the phospholipase C-ε/PLC-1 or non-muscle myosin II/NMY-1, leads to distended spermathecae occupied by one or more embryos, but does not alter tension on the basal actomyosin fibers. However, activating myosin through depletion of the Rho GAP SPV-1 increases tension on the actomyosin fibers, consistent with earlier studies showing Rho drives spermathecal contractility. On the inner surface of the spermathecal tube, tension on the apical junctions is decreased by depletion of PLC-1 and NMY-1. Surprisingly, when basal contractility is increased through SPV-1 depletion, the tension on apical junctions also decreases, with the most significant effect on the junctions aligned in perpendicular to the axis of the spermatheca. Discussion Our results suggest that much of the tension on the basal actin fibers in the occupied spermatheca is due to the presence of the embryo. Additionally, increased tension on the outer basal surface may compress the apical side, leading to lower tensions apically. The three dimensional shape of the spermatheca plays a role in force distribution and contractility during ovulation.